Companies’ communication of lifestyle with the use of brand personality - Nervén, Mattias; Pettersson, Christoffer (2009)
The purpose of this study was to clarify how companies communicate lifestyle with the use of brand personality and how it is implemented through advertising and sponsorship. To gather the information needed, a case study was carried out with three companies in Northern Sweden: Inpuls, Allstar Sportsbar, and Pite Havsbad. These cases were later compared to previous research with the purpose of identifying differences and similarities. The results of this research showed that companies communicating a lifestyle easily can apply human personality traits to their brand. Also, these companies use brand personality to a great extent in advertising to attract customers and establishing relationships with them. However, the use of sponsorship in order to establish or reinforce a brand personality was not commonly used at all among the studied companies. Validerat; 20101217 (root)